Efektivitas Model Problem Based Learning Dalam Meningkatkan Pemahaman Konsep Perbandingan Matematika Siswa Sekolah Dasar - Husni, Fadila; Adrias, Adrias; Syam, Salmaini Safitri (Universitas Nusa Cendana, 2025)
This research is based on the obstacles in understanding mathematical comparison story problems. This study aimed to see the effectiveness of the Problem-Based Learning model in improving students' ability to understand the concept of comparison story problems at SD Negeri 55 Batang Piarau. This research is quantitative with a Pre-Experimental design using a One-Group Pretest-Posttest. The results of the analysis showed that the average score increased from 75 in the pretest to 84 in the posttest. The paired sample t-test results stated that the Problem-Based Learning model was effective in improving students' concept understanding in solving word problems